Offender reentry as correctional reform: finding the boundaries of meaning in post-prison supervision - Lucken, Karol (Journal of crime and justice, 2019)
The concept of offender reentry is seen as symbolic of correctional change. However, this acknowledgement belies the fact that the concept itself, and thus the parameters of that change, have not been well-defined. Several scholars consider this ambiguity in reentry’s meaning - beyond that of change - to be problematic for operating, evaluating, and sustaining efforts advanced in the name of reentry. When viewing these potential problems against claims of correctional change, the need to examine reentry’s meaning in an applied setting becomes all the more apparent. The current study does so from the perspective of post-prison supervision professionals employed with The Florida Department of Corrections. Survey questions explore reentry’s meaning on three dimensions. They include its status as a new guiding policy, its association with rehabilitation and other goals and activities, and organizational responsibility. The findings are interpreted within the context of understanding correctional change and future policy and research.